Optimization of MSME Business Through Tiktok Influencer-Based Digital Marketing Training: Optimalisasi Bisnis UMKM Melalui Pelatihan Digital Marketing Berbasis Influencer Tiktok - Made Ary Esta Dewi Wirastuti, Ni; Made Classia Sukendar, Ni; Dian Rna Fajarini, Luh; Marcius Aquila, Brian; Wahyu Ari Wiratama, Putu; Gusti Ayu Agung Jaya Purnamasari, I (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
The food-based MSME (Micro, Small, and Medium Enterprises) sector holds significant potential in supporting economic growth, yet it still faces challenges in marketing and product quality. The Sari Mina Segara Traders Group (PSMS) in Sangsit Village, Buleleng, represents a food-processing MSME with strong potential in fish-based products but is constrained by limited marketing to local markets and simple packaging. This community service program aimed to enhance the competitiveness of PSMS through digital marketing optimization using TikTok and product packaging training. The implementation methods included socialization, digital marketing training, content creation practices, packaging technology utilization, mentoring, and evaluation. The results indicated significant improvements in participants’ skills, with 80% of members successfully producing promotional content on TikTok and 70% adopting new packaging designs that met modern market standards. The integration of digital marketing strategies and modern packaging proved effective in expanding market reach, increasing product attractiveness, and strengthening business identity. This program aligns with Sustainable Development Goals (SDGs) 8 (Decent Work and Economic Growth) and SDGs 9 (Industry, Innovation, and Infrastructure), while also supporting the Key Performance Indicators (IKU) of higher education institutions through the involvement of students and lecturers in community empowerment.